PENGARUH BOOKLET TERHADAP RESPON DAN HASIL BELAJAR SISWA MATERI UNSUR, SENYAWA DAN CAMPURAN SMP 23 PONTIANAK - Suryani, Nani; Hairida, Hairida; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this study was to examine the effect of booklet towards achievement and responses of students of SMPN 23 Ponttianak concerning topics such as elements, compounds, and mixtures. The research was carried out using nonequvalent control group design. To this test and queshionarie were used as data collections tools. the participative of this study were students at VII H grade as control and VII H as experimental group. This study began with giving a pretest to both groups. In order determine students knowledge. After a pretest was given, each group get a different treatment. Experimental group was taught with booklet. Meanwhile, control group was taught without booklet. To check student final knowledge, a posttest was given. According to U Mann Whitteny test, there wa a significant diference of achievement between students on both classes. According calculation the effect size is 0,95, which means interpreted with a high category. Student’s response towards of booklet obtained a strong average rate of approval around 86,1%. Keywords: Achievement, Booklet, Students Responses